Reinventing the Dimensions of Reading Attitude and Reading Motivation among Santri - Banatul Murtafi'ah; Nur Hidayanto Pancoro Setyo Putro (Journal of Education and Learning (EduLearn), 2018)
A large and growing body of literature has investigated students’ reading attitude and motivation either in elementary or secondary levels. Unfortunately, there remains a paucity of similar study in the context of santri or students in Islamic boarding school. This study, therefore, examined the reading attitude and motivation dimensions among santris. Three hundred and nineteen students at pesantren-based senior high schools in Yogyakarta Special Region province participated in this study by completing reading attitude survey adapted from McKenna et al. (1995; 2012) and motivational reading questionnaire (MRQ) adapted from Wigfield and Guthrie (1997). Exploratory and confirmatory factor analyses confirmed that reading attitude was represented by two dimensions as suggested by the finding in previous studies. On the other hand, instead of eleven, only seven reading motivation dimensions manifested in this present study. Reliability coefficients for all the subscales were acceptable. Finally, correlations analysis revealed that each dimension of both reading attitude and motivation were correlated positively.